2020
DOI: 10.1186/s13765-020-00541-x
|View full text |Cite
|
Sign up to set email alerts
|

The anti-obesity effect of lotus leaves on high-fat-diet-induced obesity by modulating lipid metabolism in C57BL/6J mice

Abstract: Lotus leaves (Nelumbo nucifera) are widely used in medicines and foods. The investigate systematically studied the anti-obesity effect of lotus leaf extracts. It could reduce body weight, alleviate liver damage, and inhibit fat accumulation in high-fat-diet-induced obese mice. Lotus leaf extracts reduced serum alanine aminotransferase (ALT), aspartate transaminase (AST), and alkaline phosphatase (AKP) levels; decreased total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Moreover, studies on the effect of AST and QUE on the adipogenic differentiation in human adipocytes were insufficient. Several previous studies reported that AST regulated lipogenesis and fat accumulation in 3T3-1L adipocytes via suppression of the mRNA expression of PPARγ, C/EBPα, FASN and leptin (Swamy et al, 2020;Wu et al, 2020). Similarly, QUE demonstrated significant effect against liver fat accumulation and decreased inflammatory markers in different liver injury models (Roman Junior et al, 2015;Hur et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, studies on the effect of AST and QUE on the adipogenic differentiation in human adipocytes were insufficient. Several previous studies reported that AST regulated lipogenesis and fat accumulation in 3T3-1L adipocytes via suppression of the mRNA expression of PPARγ, C/EBPα, FASN and leptin (Swamy et al, 2020;Wu et al, 2020). Similarly, QUE demonstrated significant effect against liver fat accumulation and decreased inflammatory markers in different liver injury models (Roman Junior et al, 2015;Hur et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Flavonoids and their derivatives are a class of natural compounds with abundance within the plant kingdom that exert versatile bioactivity including anti-diabetic and antiobesity effects (Lee et al, 2017;Hussain et al, 2020;Li et al, 2020;Huang et al, 2021). The beneficial properties of the flavonoids and flavonoid glycosides in diabetes and obesity management are achieved via modulation in targeted signaling networks such as the IRS/PI3K/AKT/GLUT4 pathway, thereby improving glucose metabolism, and glucose transport or aldose reductase by carbohydrate metabolic pathways in pancreatic β-cells, hepatocytes, adipocytes and skeletal myofibers (Goto et al, 2012;Lee et al, 2017;Hur et al, 2020;Hussain et al, 2020;Li et al, 2020;Wu et al, 2020;Huang et al, 2021). However, a frequently reported obstacle for the use of flavonoids in vivo is their limited bioavailability (Hussain et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other plants also regulated the serum lipid profiles, including TG, TC, ALT, AST and ALP concentration and expression of the transcription factors responsible for lipid metabolism. C57BL/6J mice were also implemented as an experimental model for Nelumbo nucifera [ 81 ], chlorogenic acid [ 82 ], Capsicum annuum [ 83 ], Cudrania tricuspidate [ 84 ], Morus alba , Ilex paraguariensis , Rosmarinus officinalis , Moringa officinalis [ 85 , 86 ], Ecklonia cava [ 47 ], Cirsium cetidens [ 87 ], Gymnema sylvestre [ 88 ] and Ishige okamurae [ 89 ], and among all these plants, the mixed extracts of Morus alba , Ilex paraguariensis and Rosmarinus officinalis showed the maximum anti-obesity effect as it decreased the body weight and relative weight of other body organs up to 98% and regulated the serum lipid profile by decreasing the TC (18.6%), LDL-c (59%), ALT (60.1%), AST (35.2%), insulin (75.9%) and leptin (46.8%). These results are maximum among the plants described above in Table 1 on C57BL/6J mice.…”
Section: Anti-obesity Effects Of Different Plant Resourcesmentioning
confidence: 99%
“…Nanoencapsulation of quercetin with a succinyl chitosan alginate shell [ 124 ] and PLGA [ 128 ] in rat models revealed that the serum lipid profile and glucose level were regulated after the induction of these nanoencapsulated structures. On the other hand, quercetin, being one of the chemical constituents in extracts of different plant parts—flowers of Capsicum annuum [ 94 ], plums of Prunus salicina [ 98 ], leaves of Vitis vinifera [ 100 ], fruits of Rhus coriaria [ 100 ], leaves of Cosmos cadatus Kunth [ 78 ], fruits of Malus prunifolia [ 102 ], fruits of Malus huphenesis [ 102 ], Hibiscus sabdariffa [ 103 ], Solenostemma argel [ 103 ], and Vibrunum opulus [ 105 ], twigs of Ranulus mori [ 111 ], leaves of Nelumbo nucifera [ 81 ], soybean embryo and enzymatically modified Isoquercetin [ 115 ]—has contributed to obesity management as mentioned above.…”
Section: Nanotechnology Associated With Anti-obesity Effectsmentioning
confidence: 99%
“…Nelumbinis folium (RN) is the lotus leaf, which is known to have the following effects: cooling of heat, smoothing of the metabolism of water in the body, clearing the blood, and removing the extravasated blood [ 13 , 14 , 15 ]. Roasted RN is a medicinal substance produced by folding the lotus leaf, placing it in a pot, sealing it with salt-rich mud, pressing it with a heavy object, and heating it to a high temperature.…”
Section: Introductionmentioning
confidence: 99%